Thermoplastic forming of additively manufactured Zr-based bulk metallic glass: A processing route for surface finishing of complex structures. (15th January 2021) - Frey, Maximilian; Wegner, Jan; Neuber, Nico; Reiplinger, Benedikt; Bochtler, Benedikt; Adam, Bastian; Ruschel, Lucas; Riegler, Sascha Sebastian; Jiang, Hao-Ran; Kleszczynski, Stefan; Witt, Gerd; Busch, Ralf
Abstract: Additive manufacturing of bulk metallic glasses (BMGs) through laser powder bed fusion (LPBF) has drawn growing interest in the last years, especially concerning industry-relevant alloys based on iron or zirconium. The process-inherent high cooling rates and localized melting pools allow to overcome geometrical restrictions given for the production of BMGs by classical casting routes. Yet, the achievable surface qualities are still limited, making an adequate post-processing necessary. In this work, we report on applying thermoplastic forming on LPBF-formed parts for the first time to decrease surface roughness and imprint finely structured surface patterns without the need for complex abrasive machining. This BMG-specific post-processing approach allows to functionalize surface areas on highly complex LPBF-formed specimens, which could be of interest especially for medical or jewelry applications. Graphical abstract: Unlabelled Image Highlights: LPBF-formed AMZ4 metallic glass provides enough thermal stability for thermoplastic forming without harsh crystallization. With adequate process parameters, thermoplastic forming has no influence on the mechanical properties of LPBF-formed AMZ4. Thermoplastic forming allows to massively reduce the surface roughness of additively formed metallic glass specimen. Finely structured surface pattern can be imprinted on additively formed metallic glass parts via thermoplastic forming.